Understanding Dworkin through art: object-based learning and law. Issue 1 (2nd January 2018) - Morgan, Lydia
ABSTRACT: This article explores object-based learning (OBL), a burgeoning pedagogical approach in higher education. Object-based learning engages students' pre-existing visual and conceptual literacy as a gateway to work through difficult threshold concepts. The article advocates this exciting learning model in law by articulating what it is, explaining how it can be applied through the example of teaching Dworkin in a jurisprudence module. The article introduces OBL approaches, details how it is relevant to jurisprudential teaching as well as its scope for application across legal teaching. It explains how such an approach moves away from transmission modes of teaching into transformational ones, accessing students' abstract web of comprehension in conjunction with text-based learning to produce more imaginative and creative critical thinking skills.